Rethinking Brand’s Presence: Universidade Federal Fluminense’s Website Project Focusing on the Users - Caio Vinicius de Macedo Goes; Lilian Soares Pinto de Souza Ribeiro (Journal of Visual Art and Design, 2016)
This article presents a redesign concept project for the main websites of Universidade Federal Fluminense, associated with Usability practices like information architecture and the application of researches to assess the usability grade of a website. The process also includes qualitative exploration with users and elaboration of guidelines that will set the future steps for the online presence of a brand.Keywords: accessibility; Universidade Federal Fluminense; website.